2022
DOI: 10.3390/toxics10060317
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Cadmium Bioaccumulation in Fresh Cow’s Milk in an Intermediate Area of the Central Andes of Peru and Risk to Human Health

Abstract: The dairy basin of the Mantaro River located in the centre of Peru faces serious anthropogenic disturbances as it receives emissions and discharges from the metallurgical mining activity located in the headwaters of the basin and milk contaminated with lead (Pb) and cadmium (Cd) endangers the environmental and human health, especially children. To measure the concentrations of Pb and Cd in milk and the dangers of their consumption in the Peruvian population, 40 milk samples were collected and quantified by ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
2
14
1
Order By: Relevance
“…The Pb contents in the forages used to feed the cows in the study area were higher than those reported in another cattle-raising area of the Mantaro Valley, which was 5.8 mg/kg [ 63 ], while the Cd level was ten times lower than those found in this study, and would be because the high amounts of phosphorous fertilizers and irrigation with water from a highly polluted canal.…”
Section: Discussioncontrasting
confidence: 81%
“…The Pb contents in the forages used to feed the cows in the study area were higher than those reported in another cattle-raising area of the Mantaro Valley, which was 5.8 mg/kg [ 63 ], while the Cd level was ten times lower than those found in this study, and would be because the high amounts of phosphorous fertilizers and irrigation with water from a highly polluted canal.…”
Section: Discussioncontrasting
confidence: 81%
“…Due to marine environmental pollution and overfishing, the wild filefish population has declined. Recently, research on filefish mainly focused on fishery resource assessments, population structure and distribution, reproductive behavior, feeding habits, artificial breeding methods, and early embryonic development [10]. There have been limited studies on the filefish's defenses against marine heavy metal pollution [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The immediate effects are a decrease in nutrients such as vitamin C and Fe, significantly affecting the immunity associated with malnutrition, while long-term effects are associated with increased cancer risks [ 127 ]. Likewise, the consumption of livestock products such as meat, milk, and eggs can be compromised when animals are fed with food from crops that have bioaccumulated heavy metals [ 128 ]. One of the foods most used in animal feed, corn, has high levels of heavy metals when planted near mine tailings [ 128 ].…”
Section: Mine Tailings Toxicity Caused By Heavy Metals and Cyanidementioning
confidence: 99%
“…Likewise, the consumption of livestock products such as meat, milk, and eggs can be compromised when animals are fed with food from crops that have bioaccumulated heavy metals [ 128 ]. One of the foods most used in animal feed, corn, has high levels of heavy metals when planted near mine tailings [ 128 ]. Figure 24 shows a conceptual diagram that summarizes all aspects related to the toxicological process and socio-environmental risks discussed in this chapter.…”
Section: Mine Tailings Toxicity Caused By Heavy Metals and Cyanidementioning
confidence: 99%